Machine learning to forecast electricity hourly LCA impacts due to a dynamic electricity technology mix - Portolani, Pietro; Vitali, Andrea; Cornago, Simone; Rovelli, Davide; Brondi, Carlo; Low, Jonathan Sze Choong; Ramakrishna, Seeram; Ballarino, Andrea (Frontiers in Sustainability, 2022)
Conventional Life Cycle Assessment (LCA) relies on static coefficients usually based on yearly averages. However, the impacts from electricity supply vary remarkably on an hourly basis. Thus, a company production plan may be reassessed to reduce selected LCA impacts due to electricity consumption. To achieve this, the company will need a forecast of hourly LCA impacts due to electricity consumption, which can be directly forecast with the Direct Forecasting (DF) approach. Alternatively, the Electricity Technological Mix Forecasting (ETMF) forecasts the electricity production of the technologies in the mix and subsequently linearly combines it with unitary LCA impact indicators. Here we assessed different machine learning models to forecast two LCA impact indicators for the consumption of electricity in the Italy-North control zone. The feed-forward neural network with ETMF approach was the best perfomer among the assessed forecasting models. In our dataset, recurrent neural networks performed worse than feed-forward neural networks. The ETMF approach was preferred over the DF approach, due to its better forecasting performance. This was due to its flexibility and scalability with easy updates or expansion of the selected forecast indicators, and due to its ability to assess technology-specific errors in the forecasting. Finally, we propose to adopt the correlation of LCA impact indicators within the dataset to select indicators while avoiding unconscious burden-shifting.